2011
DOI: 10.1111/j.1751-0813.2011.00819.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of Coxiella burnetii infection in dogs in a regional centre

Abstract: OBJECTIVE Investigate the seroprevalence of the causative agent of Q fever, Coxiella burnetii in domestic dogs in the Townsville region, North Queensland, Australia. METHOD Blood samples were collected from dogs attending veterinary clinics for routine procedures. RESULTS An overall seropositivity of 21.8% (95% confidence interval (CI) 21.6-22.1%) was observed. A retrospective study of samples collected in the same region during 1984-85 was also performed, with an overall seropositivity of 16.0% (95% CI 15.9-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 8 publications
(16 reference statements)
0
47
2
Order By: Relevance
“…The present seroprevalence was higher than that reported in new states of Federal Republic of Germany (3%, n=1620) (Kramer, 1991), North Italy (0.87%, n=802) (Baldelli et al,1992), New Zealand (0%, n=12556) (Hilbink et al, 1993) and Canada (0%, n=447) (Marrie et al, 1985), but lower than reported seropositivity in Australia (11.4%, n=201) (Cooper et al, 2011), Southern Croatia (12%, n=51) (Punda-Polić et al, 1994), Japan (15%, n=632) (Htwe et al, 1992), Nigeria (29%, n=786) (Addo & Bale, 1981), Switzerland (31%, n=388) (Metzler et al, 1983) and California (66%, n=316) (Willeberg et al, 1980). Although there is no information about Q fever in dogs population in Iran, Asadi et al (2012) reported 19.5% and 27.2% seroprevalence of C. burnetii in sheep and goats respectively (Asadi et al, 2012).…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…The present seroprevalence was higher than that reported in new states of Federal Republic of Germany (3%, n=1620) (Kramer, 1991), North Italy (0.87%, n=802) (Baldelli et al,1992), New Zealand (0%, n=12556) (Hilbink et al, 1993) and Canada (0%, n=447) (Marrie et al, 1985), but lower than reported seropositivity in Australia (11.4%, n=201) (Cooper et al, 2011), Southern Croatia (12%, n=51) (Punda-Polić et al, 1994), Japan (15%, n=632) (Htwe et al, 1992), Nigeria (29%, n=786) (Addo & Bale, 1981), Switzerland (31%, n=388) (Metzler et al, 1983) and California (66%, n=316) (Willeberg et al, 1980). Although there is no information about Q fever in dogs population in Iran, Asadi et al (2012) reported 19.5% and 27.2% seroprevalence of C. burnetii in sheep and goats respectively (Asadi et al, 2012).…”
Section: Discussioncontrasting
confidence: 47%
“…However, present research and some other previous reports showed that there was no correlation between seropositive cases and direct contact with farm animals (Gale et al, 2007;Tozer et al, 2014). It was hypothesised that other risk factors (except farm animals contact) like wildlife contact, tick exposure or pet-owners who worked closely with other farm animals would have a positive association with seropositivity to C. burnetii in the pets (Cooper et al, 2011). In present study, breed, type of housing, type of food and presence of clinical signs showed no significant differences between positive and negative cases.…”
Section: Discussioncontrasting
confidence: 43%
“…burnetii phase I or II antibodies (Cooper et al, 2011). Twenty one point eight percent of dogs tested seropositive with the most common risk factor shown to be contact with wildlife.…”
Section: Coxiella Burnetiimentioning
confidence: 99%
“…These may include common flu like symptoms such as fever, chills or sweats, fatigue, headache and muscle pain (Spelman, 1982 (McQuiston and Childs, 2002). It has been suggested that domestic pets may be a possible source of Q-fever for humans that were considered to be traditionally low risk populations (Cooper et al, 2011;Marrie et al, 1988). In Townsville, apparently healthy domestic dogs attending veterinary clinics were tested for the presence of anti-C.…”
Section: Coxiella Burnetiimentioning
confidence: 99%
“…Although Q fever has rarely been reported in children younger than 15 years, it is likely that globally, the disease is under reported in this population 60 . This is largely due to the non-specific and varied clinical presentations that occur in children infected with Coxiella.…”
Section: Pathogenesismentioning
confidence: 91%